Detection of Cervical Cancer Among Female Sex Workers - Karjatin, Atin; Sakti, Bani (Health Notions, 2018)
Cervical cancer is successfully treated when found early and followed by adequate treatment. Herein, the purpose of the research was to identify the risk of cervical cancer incidence using Ananto Sidohutomoâs questionnaire and Pap smear, which can detect the incidence of cervical cancer in female sex workers (FSW). The research used descriptive method with a sample of 30 female sex workers who checked their health atMawar Clinic. It was carried out from March to October 2015. The results show that all samples were included in the high risk category and the Pap smear result was negative for intraepithelial lesion or malignancy, which means abnormal cervical cells were not found, but Candida albicans, Bacterial Vaginosisis, and Cervixitis were found. Normal cells do not directly become cancerous cells, but first turn into abnormal cells. The change from normal to abnormal cells can be caused by exposure to germs, infections, fungi, and the like. It is suggested that preventive measures be taken to avoid cervical cancer by taking part in the screening program recommended for cervical cancer according to WHO.